Det skotske Agerbrug ved Tangaagaard. (Fortsat.) Fra 1ste April 1863 til 1ste Ap ril 1864. - Sehested, F. (Tidsskrift for Landøkonomi, 2018)
Det skotske Agerbrug ved Tangaagaard. (Fortsat.) Fra 1ste April 1863 til 1ste Ap ril 1864.